A Compelling Beginning and More to Uncover. (March 2022) - Marshak, Robert J.; Bushe, Gervase R.
The article by Hastings and Schwarz, Leading Change Processes for Success: A Dynamic Application of Diagnostic and Dialogic Organization Development (OD), deserves close review by scholars and practitioners. Their research supports arguments that OD approaches can be meaningfully categorized as diagnostic or dialogic and that differences in those approaches have significant implications for organizational change success rates. Concerns about how one assesses a leader's mindset and counterpoints to the conclusion that oscillation between diagnostic and dialogic approaches is always associated with higher success rates are presented.